2014
DOI: 10.1111/anae.12627
|View full text |Cite
|
Sign up to set email alerts
|

The use of a nasogastric tube to facilitate nasotracheal intubation: a randomised controlled trial

Abstract: SummaryDuring nasotracheal intubation, the tracheal tube passes through either the upper or lower pathway in the nasal cavity, and it has been reported to be safer that the tracheal tube passes though the lower pathway, just below the inferior turbinate. We evaluated the use of a nasogastric tube as a guide to facilitate tracheal tube passage through the lower pathway, compared with the ‘conventional’ technique (blind insertion of the tracheal tube into the nasal cavity). A total of 60 adult patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 22 publications
1
42
4
Order By: Relevance
“…It is important to consider as a result of decreased incidences of bleeding and trauma, patients will experience fewer postoperative complications such as nausea, vomiting and pain [7] [8] [16] [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to consider as a result of decreased incidences of bleeding and trauma, patients will experience fewer postoperative complications such as nausea, vomiting and pain [7] [8] [16] [17].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, providers will utilize two to three nasal trumpets to dilate the nares prior to intubation. Among Open Journal of Anesthesiology other techniques investigated for performing nasotracheal intubation involved the use of a nasogastric tube guided technique [16]. The manufacturer, Covidien, supplies nasogastric tubes to hospitals at roughly $2.95 each.…”
Section: Summary Of the Literaturementioning
confidence: 99%
“…The reason for an advantage might be the flexibility and pliability of a tube exchanger. Another study of nasotracheal intubation by Lim et al 3 showed that the pliable and flexible nasogastric tube passed preferentially through the lower aspect of the nasal passage with a preformed ETT easily advancing towards the laryngeal inlet. We hypothesized that the flexibility and pliability of a tube exchanger would be effective for nasotracheal intubation using a GVL.…”
Section: To the Editormentioning
confidence: 99%
“…Patients with head and neck cancers or trauma present functional and anatomical obstacle to nasal intubation due to potential presence of tumor, distorted anatomy and soft tissue edema. 1 The most common complication is epistaxis, although traumatic avulsion of structures within nasal fossa and nasopharynx and dissection of retropharyngeal mucosa may occur when a rigid tube tip or a sharp edged Murphys eye of nasal preformed tracheal tube passes through the narrow passages. Fibrooptic bronchoscopy is a feasible option in such patients, but it also requires training and has a learning curve.…”
Section: Introductionmentioning
confidence: 99%
“…After retrieving the NGT, the tube was easily advanced through the laryngeal inlet with the help of a fibrooptic bronchoscope as further blind intubation could impinge on the laryngeal inlet or at arytenoids cartilage and could cause traumatic bleed. 1 Thus use of NG tube at this juncture to negotiate the ETT through the nasal passage into the nasopharynx proved to be a 'rescue measure', thus facilitating fibroscopic placement of ETT in a difficult airway situation.…”
Section: Introductionmentioning
confidence: 99%